2017
DOI: 10.1128/iai.00081-17
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor Receptor-Associated Factor 6 (TRAF6) Mediates Ubiquitination-Dependent STAT3 Activation upon Salmonella enterica Serovar Typhimurium Infection

Abstract: Salmonella enterica serovar Typhimurium can inject effector proteins into host cells via type III secretion systems (T3SSs). These effector proteins modulate a variety of host transcriptional responses to facilitate bacterial growth and survival. Here we show that infection of host cells with S. Typhimurium specifically induces the ubiquitination of tumor necrosis factor receptor-associated factor 6 (TRAF6). This TRAF6 ubiquitination is triggered by the Salmonella pathogenicity island 1 (SPI-1) T3SS effectors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 50 publications
(49 reference statements)
1
16
0
Order By: Relevance
“…These data, combined with our current findings, demonstrate a coherent link between NF-kB-driven proinflammatory signaling and STAT3mediated anti-microbial pathway, which ensures defensive response at appropriate magnitude and kinetics to avoid unresolved infection (Ji et al, 2019). As an additional support, a recent study demonstrated that TRAF6, the E3 ligase required for NF-kB activation, exerted a boosting role in STAT3 activation through enhancing K63 ubiquitin (Ruan et al, 2017). Interestingly, it has been demonstrated that the deubiquitinase A20 can counteract the activity of TRAF6 through removing K63-ubiquitin from the subsets and feedback regulate vital signal pathways driven by NF-kB and TGF-b1/Smad6 (Shembade et al, 2010;Jung et al, 2013).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…These data, combined with our current findings, demonstrate a coherent link between NF-kB-driven proinflammatory signaling and STAT3mediated anti-microbial pathway, which ensures defensive response at appropriate magnitude and kinetics to avoid unresolved infection (Ji et al, 2019). As an additional support, a recent study demonstrated that TRAF6, the E3 ligase required for NF-kB activation, exerted a boosting role in STAT3 activation through enhancing K63 ubiquitin (Ruan et al, 2017). Interestingly, it has been demonstrated that the deubiquitinase A20 can counteract the activity of TRAF6 through removing K63-ubiquitin from the subsets and feedback regulate vital signal pathways driven by NF-kB and TGF-b1/Smad6 (Shembade et al, 2010;Jung et al, 2013).…”
Section: Discussionsupporting
confidence: 80%
“…In particular, our data indicate that A20 specifically interacted with STAT3 and inhibited the conjugation of K63-ubiquitin to STAT3, which in turn promoted STAT3 activation in response to staphylococcal infection. Although phosphorylation of STAT3 at Tyr705 or Ser727 has been identified as essential step for STAT3 activity, other post-translation modification and their relevance to STAT3 activation remain to be explored (Cho et al, 2019;Dallavalle et al, 2016;Ruan et al, 2017). We herein prove that de-repression of A20-mediated restraint of STAT3 ubiquitination is required for STAT3 activation and hence anti-bacterial signaling.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Thus, it is likely that through autocrine mechanisms, IL-10 also contributes to bacterial survival by blocking xenophagy. Additionally, it has been demonstrated that SopB recruits and activates TRAF6, an ubiquitin ligase responsible for STAT3 ubiquitination [58], allowing phosphorylation and activation. STAT3 is a transcription factor necessary for IL-10 production in macrophages; thus, it is possible that SopB-TRAF6 participates in IL-10 gene transcription in Salmonella -infected B cells.…”
Section: Discussionmentioning
confidence: 99%